Impact of antral follicle count on follicular–luteal characteristics, superovulatory response, and embryo quality in Sahiwal cows - Gawai, Mohan; Kumar, Brijesh; Mehrotra, S.; Chandra, Pradeep; Kohli, Kalpendra; Donadkar, Manoj; Yadav, Vandana; Yadav, Brijesh Kumar; Warghat, Chinmay; Kharayat, Nitish; Yadav, Dushyant; Singhal, Sumit; et al. (Frontiers in Veterinary Science, 2024)
The study aimed to evaluate the effect of antral follicle count (AFC) on follicular and luteal development during the estrous cycle and superovulatory period, as well as on superovulatory response and in vivo embryo quality within the MOET program. A total of 48 estrus-induced (500 μg PGF2α, Single dose, IM) Sahiwal cows (Bos indicus) with a BCS between 3.5 and 4.0 were selected for the study. On the day of wave emergence, the animals were divided into two groups based on the AFC, i.e., low AFC (≤18) and high AFC (>18). Both the groups were monitored daily using B-mode ultrasonography (USG) for one cycle, and the superovulation protocol was initiated on the 9th day of the subsequent estrous cycle. A total of 240 μg of FSH in eight divided doses were given in a tapering sequence for 4 days and simultaneous administration of 500 μg PGF2α, along with the fifth dose of FSH. Donors were inseminated at superovulatory estrus using double straws of high-quality frozen semen thrice at 12-h intervals, and non-surgical flushing was performed on day 7 of the superovulatory estrus followed by embryo searching and evaluation under a stereo zoom microscope. Ovulatory waves of the high-AFC Sahiwal cows have significantly (p ≤ 0.05) larger sizes of preovulatory follicles (POF) (12.06 ± 0.19 mm vs 11.56 ± 0.16 mm) and corpus luteum (CL) (19.57 ± 0.28 mm vs 18.26 ± 0.35 mm), as compared to low AFC. The ovarian size was significantly (p < 0.0001) larger in cows with high AFC during the superovulatory protocol. The number of large, medium, and small follicles was significantly (p < 0.0001) high on the day of superovulatory estrus (SOE), PGF2α administration, and initiation of superovulatory protocol, respectively, in high AFC. Donors with high AFC had a notably greater (p < 0.0001) count of CL and embryos retrieved per flushing, including excellent and fair-quality embryos. A strong association (p < 0.0001) between high AFC and ovarian size (r = 0.9136), superovulatory response (r = 0.9350), and embryo quality (x2 = 8.788; p = 0.032) and number (r = 0.9858) were also recorded. Based on these results, AFC is considered a dependable indicator for forecasting reproductive capacity. Bos indicus donors with an average AFC of 30 or higher are recommended.